Prevención de los problemas de conducta en el nivel inicial en la unidad educativa bilingüe la moderna CELM - Cevallos Salazar, Andrea Elizabeth (2017)
This research deals with intervention processes in behavioral problems, which are presented in the classroom of initial education in children of 3 and 4 years, these problems are associated with the experiences of the environment that the child lives from birth and the family is the one that provides mainly those experiences, the same ones that are sometimes negative and that affect the emotional development, therefore they affect the behavior and in turn the learning, causing a challenge for the teachers, to assume these problems within the classroom and that could be more severe in adult ages. For this reason the implementation of pedagogical strategies when there is interaction between the teacher and the student, allows to prevent during the teaching-learning process a behavior problem and not to suffer inappropriate behaviors in the relationship of these children with their environment……….